2013
DOI: 10.1155/2013/565096
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Indian Children with Cochlear Implant on PEACH Scale

Abstract: This study compares the functional language performance of Tamil-speaking children (n = 30) who received a cochlear implant (CI) before 2 years of age (earlier implanted group: EIG) and between 3 and 4 years of age (later implanted group: LIG). Everyday functional language of children was evaluated by interviewing parents using the adapted Parents' Evaluation of Aural/Oral Performance of Children (PEACH) Questionnaire in Tamil language. On average, both groups of children had difficulties in everyday language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…14 It was developed to test the effectiveness of auditory rehabilitation in everyday life, as traditional language testing in a structured environment may not reflect a child’s real world ability. 15 The PEACH survey has been correlated with the Preschool Language Scale (PLS-4), Peabody Picture Vocabulary Test (PPVT), Diagnostic Evaluation of Articulation and Phonology (DEAP), and Child Development Inventory (CDI), 16 and has been deemed a reliable measure of parental observations. 14, 17 This survey requires healthy children that are using a functional implant at the time of survey.…”
Section: Methodsmentioning
confidence: 99%
“…14 It was developed to test the effectiveness of auditory rehabilitation in everyday life, as traditional language testing in a structured environment may not reflect a child’s real world ability. 15 The PEACH survey has been correlated with the Preschool Language Scale (PLS-4), Peabody Picture Vocabulary Test (PPVT), Diagnostic Evaluation of Articulation and Phonology (DEAP), and Child Development Inventory (CDI), 16 and has been deemed a reliable measure of parental observations. 14, 17 This survey requires healthy children that are using a functional implant at the time of survey.…”
Section: Methodsmentioning
confidence: 99%
“…While, several studies have reported that children who receive CI at a very younger age are expected to attain superior speech and language skills than children who receive CI at a later age [10,16,17], there was no significant difference noticed in terms of auditory and communicative performance between children who received CI in the age range of 2 to 3 years (EIG) and children who received CI in the age range of 4 to 5 years (LIG) in the present study. Although the children of LIG received CI in the age range of 4 to 5 years, they had 2 to 3 years of pre-implant intervention with HAs, in addition to 5 to 6 years of post-implant CI use.…”
Section: Discussionmentioning
confidence: 99%
“…Several questionnaires and/or inventories have been developed for evaluating children's auditory related skills and the relative effectiveness of their hearing devices [8]. The necessity of including wider outcome measures, especially the parental reports while assessing the outcomes of children with CI has been emphasized [9][10][11]. Based on the high grades received in a critical review of subjective outcome evaluation questionnaires, the Parents' Evaluation of Aural/Oral Performance of Children (PEACH) scale [8] was found one of the more appropriate [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies based on the exploring of CI outcomes. The views of parents on CI and the parents' expectation from children using CI, was based on the parent questionnaire (Kumar et al, 2013;Kumar et al, 2017;Archbold et al, 2008). In these studies, parents completed the questionnaire and their responses were analyzed.…”
Section: How To Cite This Articlementioning
confidence: 99%